Genetic Variant in Long Non-Coding RNA H19 Modulates Its Expression and Predicts Renal Cell Carcinoma Susceptibility and Mortality - Cao, Qiang; Li, Pengchao; Cao, Pu; Qian, Jian; Du, Mulong; Li, Li; Wang, Meilin; Qin, Chao; Shao, Pengfei; Zhang, Zhengdong; Lu, Qiang; Wang, Zengjun (Frontiers in Oncology, 2020)
The long non-coding RNA (lncRNA) H19 has been demonstrated to play a crucial role in carcinogenesis, including renal cell carcinoma (RCC). However, the impact of genetic variations in H19 gene on RCC has not been investigated before. In the present study, we sought to evaluate whether genetic polymorphisms in H19 are related to the susceptibility and mortality of RCC. We genotyped four widely studied polymorphisms in H19 and assessed their relationship with susceptibility and prognosis of RCC in a case-control study compromising 1,027 cases and 1,094 controls. The functionality of the important polymorphism was further investigated by real-time polymerase chain reaction and luciferase reporter assay. We found that H19 rs2839698 was significantly associated with risk and prognosis of RCC. Compared with the H19 rs2839698 CC genotype, the variant genotypes (CT/TT) were significantly associated with increased risk of RCC (P = 0.023, OR = 1.21; 95% CI = 1.03–1.45). Besides, patients with variant genotypes (CT/TT) were more likely to develop large tumor (P = 0.003, OR = 1.47; 95% CI = 1.16–1.85) and advanced disease (P = 0.010, OR = 1.59; 95% CI = 1.12–2.26); and had a significantly unfavorable overall survival than those with the rs2839698 CC genotype (CT/TT vs. CC: Log-rank P = 0.026, HR = 2.25, 95%CI = 1.07–4.75). Furthermore, the CT/TT genotypes were associated with significantly increased expression of H19 in renal tissue. The luciferase reporter assays revealed the potential effect of rs2839698 variant on the binding of microRNAs to H19. Our results suggest that the H19 rs2839698 variant may be a genetic predictor of susceptibility and mortality of RCC. The risk effects and the functional impact of the variant on H19 still need further validation.